Academic Field Trip as a Teaching Pedagogy to Accounting Students - Mohammad, Hapsah S. (UUM Press, 2018)
Academic field trip is organised to attain several objectives. The objectives are in general, among others, to enhance social, personal and emotional development of students as well as to add value to students academic development. However, the specific objectives, as outlined in the syllabus of strategic management courses, include ability to function as a consultant, owner of a business, make strategic decisions and to justify those decisions through oral and written communication, both as an individual and as a member of a team. To meet these objectives, general and specific, at the beginning of the semester, students are briefed about the academic field trip and expectation (knowledge and experience) from it. To ensure that the students will benefit from the trip, they are required to make some preparations before going for the academic field trip. The preparation includes research on the company and its industry, and to get the necessary information during the trip in order to complete some tasks. To complete the tasks, students have to form groups of three and they are given some assignments. The information necessary to complete the assignment will come from their observations during the trip. Basically, the assignments relate to the concepts and theories they have learned in class. The assignments will reflect the ability of the students to link them to the industry. Thus, the objective of this paper is to discuss the preparation before, during and after field trip as a teaching pedagogy in line with output-based education system. However, the effectiveness of academic field trips as a teaching pedagogy is not measured directly, therefore, it becomes a limitation of the paper. Nevertheless, this paper may serve as a useful input in the involvement and commitment of students during fieldtrips and the content of the assignment submitted will give an insight into the level of understanding of the students on class-room learning.